Genetic heterogeneity of congenital cerebral palsy and the concept of the neurotropic genome - P. L. Sokolov; N. V. Chebanenko; A. G. Prityko; P. A. Romanov (Русский журнал детской неврологии, 2023)
Background. Currently, more than 500 genes are known, in one degree or another associated with the development of the phenotype of congenital cerebral palsy (CP). The amount of accumulated data requires the sorting of the mechanisms of the influence of genes on brain development.Aim. To compare the spectrum of determinants in groups of patients with CP, accompanied (CP+) and non-accompanied (CP–) by epilepsy.Materials and methods. 154 children with a phenotype of cerebral palsy aged from 1 to 17 years old were investigated. Boys – 92, girls – 62. Genetic mutations were confirmed by the methods of next generation sequencing (NGS) in the study of venous blood samples. Genes with anomalies were distributed to the groups of determinants for the main aspects of the development and function of the brain. A total of 13 groups were created.Results. In the CP– group, determinants of cell dividing, brain development and cytoskeleton were identified in 11 (61.1 %) cases. In 4 (22.2 %) cases, determinants of cell metabolism and external cell membrane transport were identified. In the CP+ group in 23.5 % of cases, determinants of cell division, brain development and cytoskeleton were revealed. The number of patients with anomalies of chromatin modifications, transcription and replication processes was significantly less (4.4 %). In 42 (30.8 %), the CP+ patients found determinants of excitability of the neuronal membrane and excitation transmission. In the cases of brain malformations in both CP– and CP+ groups determinants of cellular division, brain development and cytoskeleton were identified. Interest caused cases of brain malformations with anomalies of genes of the channelopathy.Conclusions. Our data suggests the difference between pathogenetic models CP+ and CP–. The fundamental difference of them is the presence of genes regulating the excitability of the neuronal membrane in CP+ group.